Contributing Factors to the Progress of Inclusive Education Implementation in Indonesia - Cabatay, Mulina; Hermanto, Hermanto; Aningrum, Rizki (INKLUSI, 2024)
Indonesia made its commitment clear to obtain education for all its citizen without discrimination. However, the research-to-practice gap remains in terms of the implementation of inclusive education in the country. Therefore, this scoping review aimed to describe the current progress of the country’s inclusive education implementation efforts through the previous literature. A total of 20 articles were included in this review. The findings showed that an increasing number of studies report on Indonesia’s progress in the implementation of inclusive education in terms of inclusive, innovative, and integrated learning programs, improvement of teachers’ competence, collaboration efforts, society’s respect towards persons with special needs and disabilities, and several challenges serve as a room for improvement. Factors contributing to the gradual progress of the country’s inclusive education implementation are teacher competence and awareness about inclusive education, good government support, multi-sectoral collaboration and coordination, profound legal support, and student-focused strategies.